The Overview of the Elderly Lifestyle Profile in Surabaya - Yuliastuti, Christina; Anggoro, Sapto Dwi (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
The elderly lifestyle may affect their health condition. Based on SUSENAS 2014, the number of elderly in Indonesia reached 20.24 million, with 25.05% morbidity rates, it shows that one in four elderly people have experienced some illness. This study aimed to identifying the lifestyle profile of the elderly in Surabaya. The research design used descriptive method with variable of lifestyle of 210 elderly in Surabaya. This study was conducted from June until July, 2016. The results showed that the elderly living in coastal areas having poor lifestyle (53,256 + 11,6719), while elderly living in urban areas and in nursing homes having moderate lifestyle (66,680 + 9,3923) and (62,347 + 7,8814), respectively. Poor lifestyle found in coastal areas of Surabaya was due to lacking of physical exercise and ignorance of diet pattern. Family as a major support system should provide assistance and attention.